(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The lack of standard practices and platforms for assessing refurbishment strategies towards Circular Economy (CE) and their impact in global warming constitutes a challenge for the decarbonization of existing building stock. Incorporating data and feedback from designers and practitioners since early design stages is important to feed a multi-criteria dynamic process with multiple dimensions, which must be assessed under a life cycle perspective. To tackle this issue, this paper introduces a new methodology to support the implementation of tailored refurbishment strategies for increased recovery, reuse and recycling of construction materials. The final objective is to build a methodological framework for sustainable refurbishment design in a BIM environment, which aims to facilitate standardized practices in the construction sector, regarding CE, with a positive impact in the mitigation of global warming and the decarbonization of the building stock. To test the development of this methodology, a case study building in Lisbon, corresponding to a 1919 - 1945 archetype is analysed, making use of its BIM model, where BIM standardization criteria and circularity indicators are discussed, in order to be implemented as a Plugin for Circularity.